Antibacterial Effect Of Ocimum Tenuiflorum And Plectranthus Amboinicus Extracts Against Methicillin-Resistant Staphylococcus Aureus (Mrsa) And Staphylococcus Aureus (Sa) Isolates - Santhini Venggadasalam (2024)
An abstract of the research paper presented to the Faculty of Veterinary Medicine, Universiti Malaysia Kelantan, in partial requirement of the course DVT 55204 – Research Project. The growing frequency of antibiotic-resistant bacteria, including methicillin-resistant staphylococcus aureus (MRSA), warrants the investigation of alternative antimicrobial agents. This study evaluates the antibacterial inhibitory effects of methanolic extracts of Ocimum tenuiflorum and Plectranthus amboinicus against staphylococcus aureus (SA) and MRSA isolates using the disc diffusion method. Statistical analysis using one-way ANOVA revealed significant differences in the antibacterial inhibitory effects among treatment groups for both SA (F(7,16) = 433.96, p < 0.001) and MRSA (F(7,16) = 304.70, p < 0.001). Among individual extracts, P. amboinicus exhibited the highest antibacterial inhibitory effect, with inhibition zones averaging 1.1 cm for SA and 1.0 cm for MRSA, attributed to bioactive compounds such as thymol and carvacrol. Combined extracts displayed synergistic antibacterial inhibitory effects, particularly with higher concentrations of P. amboinicus, but their efficacy was lower compared to selected commercial antibiotics, including enrofloxacin, cefoxitin, and gentamicin. These findings highlight the potential of plant-based antimicrobials, particularly P. amboinicus, as alternative therapies for multidrug-resistant pathogens. Future studies should focus on optimizing extraction protocols and elucidating the molecular mechanisms underlying their antibacterial properties. Keywords: Ocimum tenuiflorum, Plectranthus amboinicus, staphylococcus aureus, methicillin-resistant staphylococcus aureus, antibacterial effect, plant-based antimicrobials